Studi Kasus Penilaian Kelaikan Kerja Pasca Stroke Non Hemoragik pada Security Pos Limbah Pabrik Sepatu - Dewi Indah Lestari (Jurnal Kesehatan Amanah, 2025)
Stroke or cerebrovascular disease (CVA) is an acute disorder of cerebral or blood vessel perfusion. About 85% of strokes are ischemic and the rest are hemorrhagic. Stroke is the main cause of disability in adults throughout the world. Since 1990-2019, there has been an increase in the incidence of stroke by 70%, of which 40% of cases resulted in death. CVA is also one of the causes of sick leave in the working population. largest and low return to work rates among workers.  It is important to carry out a work fitness assessment before returning to work. This assessment is carried out thoroughly and comprehensively, which includes examination of the physical, mental condition and also aspects of the work, including job descriptions, work demands, and the environment to readjust the worker's health condition to the work aspects. A 35 year old woman, working as a security team at a shoe factory security post, experienced a non-hemorrhagic stroke with weakness on the left side of the body, spoke slurredly after the second bilateral hysterec-salphingo oovorectomy 3 days previously. The work fitness assessment was carried out by following up on the patient's clinical condition, where 10 weeks after the stroke, this patient was declared fit to work with a Fit With Note. Limitations on the length/duration of work in the form of overtime and a shift work system are implemented so as not to increase the patient's workload.